Characteristics of seismic motions at a concrete gravity dam site and suggestions for setting the engineering bedrock. Issue 4 (November 2021) - Yasuda, Nario; Cao, Zengyan
The earthquake records of a concrete gravity dam with eight seismographs were spectrally analyzed to clarify the characteristics of the seismic motions at each monitoring station. Based on the analysis results, whether it is appropriate to use such earthquake records to generate the input ground motion in assessments of the seismic performance of dams was discussed. It was found that the earthquake records at the dam base show reduced amplitudes at frequencies corresponding to the natural vibration modes of the dam. When these earthquake records are used to generate the input ground motion in an assessment of the seismic performance of a dam, sufficient consideration should be given to this feature. Suggestions on where to install seismographs at dam sites are presented. Based on the numerical simulation of the seismic response of the dam, it is suggested that the engineering bedrock should be considered to be located at a depth of at least 1.5 times the dam height, and the shear wave velocity of the rock at that depth should preferably be 2000 m/s or more. Since this study uses seismic motions recorded across the entire dam site, including the deep rock, which is globally rare, it is considered that the basic conclusions obtained in the article can provide a reference for other concrete dams.